A Case Report of Inherited DYRK1A Neurodevelopmental Syndrome - Abumansour, Iman S; Almatrafi, Mohammed H; Almutadares, Mahmoud N; Khogeer, Asim A (Archives of Clinical and Medical Case Reports, 2023)
DYRK1A disorder is among the most frequent monogenic forms of intellectual disability (ID). The majority of cases have been reported to be due to de novo pathogenic variants in DYRK1A gene. This report describes the second case of inherited DYRK1A syndrome that had created issues around variant classification due to its inheritance from an apparently healthy mosaic mother.